Accepting the invisible hand market-based approaches to social-economic problems - White, Mark D. 1971- (Perspectives from social economics, 2010)
This collection of essays by prominent economists and philosophers showcases the important contributions that markets can make to important topics within social economics, including practical issues such as poverty and disaster relief, as well as more general concerns regarding ethics and well-being